Meeting the Standards in Primary ICT - Higgins, Steve (Taylor & Francis, 2004)
This practical guide to using ICT in the primary classroom addresses all the concerns of student teachers and provides plenty of ideas and advice on how to incorporate ICT into classroom practice on a daily basis. The authors bring together theory and practice to help prospective and new teachers acquire and develop the skills required for using ICT effectively. Meeting the Standards in Primary ICT is split into three sections which will: help assess the readers' ICT skills, knowledge and understanding discuss ways of incorporating ICT for teaching across the primary curriculum help the reader to think about ICT and their own professional learning and development. This book will be an invaluable resource for all student teachers on primary training courses, lecturers and mentors supporting trainees on these courses and newly qualified teachers (NQTs).